Segregation of EAV-HP Ancient Endogenous Retroviruses within the Chicken Population - Sacco, M. A. (American Society for Microbiology, 2001)
Avian leukosis virus subgroup J (ALV-J), an exogenous avian retrovirus, is thought to have evolved by recombination with the highly identical env gene of the endogenous avian retrovirus EAV-HP. Embryonic expression of EAV-HP env has been suggested to be associated with the induction of immunological tolerance, a feature observed in a significant proportion of meat-type chickens infected with ALV-J. In support of this hypothesis, we demonstrate that EAV-HP loci, some of which could be associated with tolerance, are still segregating within the chicken population.